Examination of the literacy attitudes of rural male adolescents - Montgomery, Jennifer R. (Kansas State University, 2010)
Much recent scholarship about boys and literacy focuses on the “crisis” of male underachievement in schools, and a number of authors address why boys’ literacy rates are low (e.g., Newkirk, Wilhelm and Smith). In this paper, I use current scholarship and primary research to examine the literacy ideology of a specific group of adolescents who are underrepresented in the literature: those living in rural areas. Using interviews from eight high school boys as case studies, I examine how literacy manifests itself in male adolescents from the rural Midwest. This study follows a qualitative empirical methodology. I find that the boys’ ideology is shaped by societal and familial influences and is essentially a “serviceable” literacy ideology. A serviceable literacy is rooted in a male identity or “habitus,” which refers to the way individuals perceive, assess, and act in the world (Bourdieu, “Habitus”). The findings in this study suggest that rural young men have a habitus characterized by independence, expediency, competition, and individuality. Complicating this habitus of young rural men is a stigma that some of the boys are very aware of. This stigma asserts that rural inhabitants value literacy less than middle- and upper-class urban inhabitants. My findings clearly demonstrate that people who live in rural areas are certainly literate and value literacy, but school-sponsored literacy is very different than serviceable literacy, and classrooms are the arena for a struggle as educators attempt to expose students to unfamiliar forms of reading. Therefore, the results of this study present pedagogical challenges for rural English teachers who are responsible for literacy instruction. Lastly, I will present some solutions found in the literacy scholarship.
Keywords: Literacy; Rural males; Adolescent; Reading; Masculine identity; Stigmatization; Education, Reading (0535); Language, Rhetoric and Composition (0681)